1986
DOI: 10.1002/pc.750070612
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical behavior and structure of ternary blends of polypropylene/EPDM rubber/polyethylene

Abstract: The dynamic mechanical behavior of ternary blends of isotactic polypropylene (80–0 percent)/EPDM rubber (20 percent)/high‐density polyethylene (0–80 percent) was investigated in the temperature range from −196 to 100°C by means of a free‐oscillating torsional pendulum. The structure of the blends was examined by a scanning electron microscope on etched surfaces cut by a fractured glass edge in liquid nitrogen. Dynamic mechanical response spectra and microphotographs of the systems studied show that the minor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Experimentally, it has been reported that EPR and EPDM are somewhat more miscible with PE than PP and there is some indication of an interpenetrating structure between EPR and PE 24. Kolarik et al examined the dynamic mechanical properties of binary and ternary blends of PP, PE, and EPDM, and reported 20 vol% of EPDM could accommodate 20 to 30 vol% of HDPE 25, 26. Since the EPR content in HPC used in this study is 11 wt%, it is expected from 10 to 15 wt% HDPE could reside inside the EPR dispersed phase.…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, it has been reported that EPR and EPDM are somewhat more miscible with PE than PP and there is some indication of an interpenetrating structure between EPR and PE 24. Kolarik et al examined the dynamic mechanical properties of binary and ternary blends of PP, PE, and EPDM, and reported 20 vol% of EPDM could accommodate 20 to 30 vol% of HDPE 25, 26. Since the EPR content in HPC used in this study is 11 wt%, it is expected from 10 to 15 wt% HDPE could reside inside the EPR dispersed phase.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile modulus of two-component systems modeled by the EBM (Fig. 1) reads [19,25,26,[28][29][30]…”
Section: Predictive Schemementioning
confidence: 99%
“…Such models could be applied to polymer blends, but only in the marginal composition intervals where the minority component is fully discontinuous. Recent studies [28][29][30][31][32][33][34][35][36][37] have shown that the minority component in two-component heterogeneous blends exhibits partial continuity at the critical volume fraction as low as 0.1 < v cr < 0.2. Consequently, the minority component at v > v cr starts to affect blend properties relatively more than in a fully dispersed state.…”
Section: Introductionmentioning
confidence: 99%
“…Physical properties of blends consisting of a continuous matrix and one or more dispersed (discrete) components can be predicted by using adapted models proposed for particulate composite systems (216)(217)(218)(219)(220). Most of these models do not consider effects of the particle size, but only of volume fractions of components in the system.…”
Section: Predictive Formats For Selected Physical Propertiesmentioning
confidence: 99%